A Perfect Ground: preparatory layers for oil paintings 1550 - 1900 Maartje Stols-Witlox - Bruquetas Galán, Rocío (Ge-conservacion, 2018)
Perfect Ground: preparatory layers for oil paintings 1550 - 1900Maartje Stols-WitloxISBN: 9781909492356Dimensiones: 246 x 175mmPáginas: 412Ilustraciones en color